2018
DOI: 10.1051/0004-6361/201730656
|View full text |Cite
|
Sign up to set email alerts
|

First analysis of solar structures in 1.21 mm full-disc ALMA image of the Sun

Abstract: Context. Various solar features can be seen in emission or absorption on maps of the Sun in the millimeter and submillimeter wavelength range. The recently installed Atacama Large Millimeter/submillimeter Array (ALMA) is capable of observing the Sun in that wavelength range with an unprecedented spatial, temporal and spectral resolution. To interpret solar observations with ALMA the first important step is to compare solar ALMA maps with simultaneous images of the Sun recorded in other spectral ranges. Aims. T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 55 publications
7
39
0
Order By: Relevance
“…The availability of millimeter-λ solar observations with Atacama Large Millimeter/submillimeter Array (ALMA) has the potential to provide new insights into the physics of the chromosphere thanks to the superior spatial and temporal resolution and sensitivity of the instrument. Observations of the quiet Sun with ALMA have been reported by Shimojo et al (2017a,b), White et al (2017), Alissandrakis et al (2017b), Bastian et al (2017), Yokoyama et al (2018), Nindos et al (2018), Loukitcheva et al (2019), Brajša et al (2018), Jafarzadeh et al (2019), Selhorst et al (2019), Molnar et al (2019), Patsourakos et al (2020), andWedemeyer et al (2020). Among those articles, detection of single weak transient events was reported by Shimojo et al (2017b), who studied a plasmoid ejection associated with an X-ray bright point, and by Yokoyama et al (2018) who reported jet-like activity at 3 mm.…”
Section: Introductionmentioning
confidence: 90%
“…The availability of millimeter-λ solar observations with Atacama Large Millimeter/submillimeter Array (ALMA) has the potential to provide new insights into the physics of the chromosphere thanks to the superior spatial and temporal resolution and sensitivity of the instrument. Observations of the quiet Sun with ALMA have been reported by Shimojo et al (2017a,b), White et al (2017), Alissandrakis et al (2017b), Bastian et al (2017), Yokoyama et al (2018), Nindos et al (2018), Loukitcheva et al (2019), Brajša et al (2018), Jafarzadeh et al (2019), Selhorst et al (2019), Molnar et al (2019), Patsourakos et al (2020), andWedemeyer et al (2020). Among those articles, detection of single weak transient events was reported by Shimojo et al (2017b), who studied a plasmoid ejection associated with an X-ray bright point, and by Yokoyama et al (2018) who reported jet-like activity at 3 mm.…”
Section: Introductionmentioning
confidence: 90%
“…While the first regular ALMA observations of the Sun were only offered in Cycle 4 with a first solar campaign in December 2016, earlier observations from Commissioning and Science Verification (CSV) campaigns have been made publicly available. Both regular and CSV data are already used in publications: Alissandrakis et al (2017), Bastian et al (2017), Shimojo et al (2017b), Brajša et al (2018), Nindos et al (2018), Yokoyama et al (2018), Jafarzadeh et al (2019), Loukitcheva et al (2019), Molnar et al (2019), Rodger et al (2019), Selhorst et al (2019), Patsourakos et al (2020), da Silva Santos et al (2020.…”
Section: Introductionmentioning
confidence: 99%
“…The Atacama Large Millimeter/Submillimeter Array (ALMA, Wootten & Thompson 2009) has overcome the spatial resolution limitations that observing at such long wavelengths entails. ALMA has shown that the landscape of the solar surface at 1 mm is marked by relatively cooler regions such as the QS and sunspot umbras, and hotter features such as plage regions (Loukitcheva et al 2017;Brajša et al 2018), and that the brightness of the mm continuum correlates with that of the Mg ii lines (Bastian et al 2017(Bastian et al , 2018Jafarzadeh et al 2019). However, the large scatter and offset between the two diagnostics is evidence for NLTE effects in the Mg ii lines that make them only partially sensitive to the chromospheric temperatures (e.g., Leenaarts et al 2013a), although there may also be systematic differences in their formation heights (e.g., da Silva Santos et al 2018).…”
Section: Introductionmentioning
confidence: 99%